Insulin-like growth factor-i and risk of differentiated thyroid carcinoma in the European prospective investigation into cancer and nutrition. - Schmidt, J; Allen, N; Almquist, M; Franceschi, S; Rinaldi, S; Tipper, S; Tsilidis, K; Weiderpass, E; Overvad, K; Tjønneland, A; Boutron-Ruault, M; Dossus, L; et al. (American Association for Cancer Research Inc., 2014)
BACKGROUND: Little is known about the causes of thyroid cancer, but insulin-like growth factor-I (IGF-I) might play an important role in its development due to its mitogenic and antiapoptotic properties. METHODS: This study prospectively investigated the association between serum IGF-I concentrations and risk of differentiated thyroid carcinoma in a case-control study nested within the European Prospective Investigation into Cancer and Nutrition. The 345 incident cases of differentiated thyroid carcinoma were individually matched to 735 controls by study center, sex and age, date, time, and fasting status at blood collection, follow-up duration, and for women menopausal status, use of exogenous hormones, and phase of menstrual cycle at blood collection. Serum IGF-I concentrations were measured by immunoassay, and risk of differentiated thyroid cancer in relation to IGF-I concentration was estimated using conditional logistic regression. RESULTS: There was a positive association between IGF-I concentrations and risk of differentiated thyroid carcinoma: the OR for a doubling in IGF-I concentration was 1.48 (95% confidence interval, 1.06-2.08; Ptrend = 0.02). The positive association with IGF-I was stable over time between blood collection and cancer diagnosis. CONCLUSION: These findings suggest that IGF-I concentrations may be positively associated with risk of differentiated thyroid carcinoma. IMPACT: This study provides the first prospective evidence of a potential association between circulating IGF-I concentrations and risk of differentiated thyroid carcinoma and may prompt the further investigations needed to confirm the association.